The making of a Reformation man - Whitford, David M. (David Mark), author. Link
1 online resource (258 pages)
Keywords: This volume explores how Martin Luther's life and teachings reshaped and redefined masculinity during the Reformation, offering a more nuanced portrayal of him as a man grappling with the complexities of fatherhood, marriage, and the battlegrounds of religious controversy.This book demonstrates how Luther forged a new ideal of Christian manhood by examining his struggles with monastic vows, his transformation of the household as a spiritual center, and his reshaping of male authority. Integrating insights from cultural historians, gender studies, and feminist scholarship, Whitford analyzes the intersections of gender, power, and religion during a time of profound social upheaval and change. Through Luther's personal transformation, this book reveals how early Protestant ideals of masculinity were intricately tied to broader religious, political, and cultural changes that reshaped Europe. By placing Luther within the wider context of religious and social transformation, this work offers a fresh perspective on his impact and the changing notions of masculinity in the early modern period.The Making of a Reformation Man is a valuable resource for scholars and students of the Reformations and gender theory, as well as readers interested in the broader implications of religious thought on societal roles and identity.